HARMONI WARIS ISLAM DAN SUNDA - Abdurrahman Misno Bambang Prawiro (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2015)
The sharing of the property inheritance has been set perfectlv by Islamic teaching as the perfect Islamic law. It includes in the Faraidh that comprehensively addresses the laws relates to the system of inheritance in Islam. The discussion include the wills, the definition of inheritance, the source of Islamic law, pillars and conditions of the inheritance, the causes of inheritance, the heirs and their shares, barriers of inheritance and problems of inheritance that has no basic regulation in the al-Quran and al Sunnah. As a revelation that comes from Allah, the Islamic inheritance system is the laws that must be implemented by all Muslims. The rules have been standard so there is no reason to reject it. Key words: Sundanese inheritance, Islamic inheritance, Jahiliyyah inheritance